Exploring medicinal potential and drug delivery solutions of Celastrol from the Chinese "Thunder of God Vine" - Ren, Zimo; Coghi, Paolo (European Journal of Chemistry, 2024)
Tripterygium wilfordii (TRWI), known as 'Thunder of God Vine' or 'Lei Gong Teng' in traditional Chinese medicine (TCM), is a perennial vine that has been used for centuries for its potent therapeutic properties. This plant, which belongs to the Celastraceae family, has been documented in various TCM texts, where it has been attributed with a wide range of benefits, including anti-inflammatory, antirheumatic, and anti-autoimmune activities. Central to the medicinal potential of TRWI is celastrol, a triterpenoid with extensive pharmacological activities. Research on celastrol has revealed its effects on combating inflammation, oxidative stress, cancer proliferation, and neurological disorders. However, celastrol’s high toxicity, low water solubility, and limited stability pose challenges for its clinical application. In this review, we explore the chemical structure of celastrol, emphasizing its key pharmacological activities and the structure-activity relationships (SARs) that influence its efficacy and toxicity. Various studies have demonstrated that modifications at specific sites, such as the C-29 carboxylic group, C-6, and C-3, can enhance celastrol’s therapeutic potential while reducing adverse effects. Moreover, recent advances in drug delivery systems offer promising avenues to overcome the inherent limitations of celastrol. These include direct modifications such as PEGylation and indirect modifications through encapsulation in dendritic polymers, phytosomes, liposomes, and exosomes. Each method seeks to improve celastrol bioavailability, water solubility, and target capabilities, thus enhancing its clinical viability. The objective of this review is to synthesize current knowledge about celastrol’s therapeutic potential and discuss the future of its development in drug delivery and pharmaceutical applications. These findings could open the door to new treatment methods that combine traditional remedies with modern pharmacology, helping us unlock the complete potential of celastrol in clinical use.